Examining the Characteristics of Generation Z and Their Implications for Students' Character Education - Nasrudin, Ega; Sumarna, Elan; Surahman, Cucu (UIN Sunan Gunung Djati Bandung, 2024)
This study examines the characteristics of Generation Z as digital natives along with their implications for character education. This study is important to carry out considering that each generation has its own characteristics that distinguish it from other generations, especially in the education process. The research method used in this study is a literature study with the stages of reviewing, collecting, and analyzing these references. The results of this study indicate that Generation Z has a variety of uniqueness compared to other generations. The most prominent uniqueness of this generation is their ability and habits in using technology. In addition, this generation is also known as a generation that is more creative and innovative, has social responsibility, is active, likes to seek comfort, prioritizes security, is easy to connect with each other, and other characteristics. The uniqueness of Generation Z brings changes to various aspects of life, including the character education process. The character education process is considered still very necessary for this generation. Character education for this generation can be carried out through the family environment, school environment, and community environment. Character education in the family environment emphasizes more on the use of good approaches and the creation of a harmonious family environment. Meanwhile, education in the school environment for Generation Z can be implemented by choosing a variety of strategies, approaches, and learning models that are right for this generation. As for character education through the current community environment, it can be done by creating religious character posts that are uploaded to the internet via social media. This study recommends that subsequent researchers conduct character education experiments in the school, family, or community environment. Contribution: By identifying the characteristics of Generation Z, the research highlights the need for educational approaches that cater to their specific needs. This includes adapting teaching methods to incorporate technology and interactive learning experiences that resonate with their digital upbringing.